Reflux in young patients: comparison of voiding US of the bladder and retrovesical space with echo enhancement versus voiding cystourethrography for diagnosis - Kassa Darge; Tröger, Jochen; Dütting, Tanja; Zieger, Birgit; Rohrschneider, Wiltrud; Möhring, Klaus; Weber, Christian; Tönshoff, Burkhard (Radiology, 1999)
To compare the usefulness of voiding US of the bladder and retrovesical space with echo enhancement with that of voiding cystourethrography (VCUG) for diagnosis of vesicoureteral reflux (VUR) and to assess patient tolerance of the echo-enhancing agent.
Gesehen am 26.01.2021